Penggunaan Media Gambar Kartun Dalam Pembelajaran Bahasa Inggris Sekolah Dasar Untuk Meningkatkan Hasil Belajar - Ibda, Hamidulloh; Prabandari, Lestari Tunjung; Al-Hakim, Muhammad Fadloli (Balai Diklat Keagamaan Surabaya, 2023)
English language learning in primary schools is still not optimal. This is because English is not given explicitly. This factor makes children's interest in learning English decrease. Therefore, teachers are required to make English learning more fun and attract children's attention by adding a variety of learning media in the teaching and learning process. This research is a Classroom Action Research, which is research conducted in the classroom with an emphasis on improving or enhancing learning processes and practices. The application of learning media Cartoon Pictures can improve student learning outcomes on the material Jobs and Professions. In detail, the increase in the percentage of completeness of student learning outcomes in cognitive aspects can be seen in cycle I which in the initial condition only amounted to 31.57% increased to 73.68%. After the action was taken again in cycle II, the percentage of completeness of student learning outcomes also increased to 100%. Furthermore, an increase also occurred in the percentage of learning outcomes in the affective aspect in cycle I of 68.24% of students in the good and very good categories, increasing to 84.21% of students in the good and very good categories. Future research needs to explore the use of cartoon media in English language learning in elementary schools in various materials.